Is Political Consulting Going Digital?. Issue 1 (2nd January 2017) - Cacciotto, Marco M.
Abstract : Every four years consultants all over the world look at American presidential elections trying to unveil new techniques that can be adopted in their own countries. In 2012 databases and metrics become the cornerstone for a successful campaign and therefore, there is a need for new professionals, and for a new way of approaching the profession. The campaign for the re-election of Obama residential is a turning point not only for political communications but also for political consulting: digital revolution will open doors for a new generation of consultants not only in the United States, but also in Europe and South America.